Analisis Gaya Mengajar Dan Fasilitas Yang Digunakan Oleh Guru Dalam Proses Pembelajaran PPKN Di SMP Negeri 35 Medan - San Mikael Sinambela; Johan Pardamean Simanjuntak; Mima Defliyanti Saragih; Manotar Leryaldo Sinaga; Chairun Nisa; Muthi’ah Lathifah (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
This research was conducted with the aim of finding out the teaching style of Civics Teachers at SMP N 35 Medan and to find out what facilities the teacher uses when teaching in class.This research method is to use a descriptive qualitative method using a field study approach. The results of this research show that the PPKn teachers at the school use an interactional teaching style and the learning facilities used are quite simple, such as the use of blackboards, study tables and PPKn package books.The conclusion is that the teacher has taught according to the RPP that has been prepared and he teaches well and with quality.